P-9 Autoimmune liver diseases in Latin America: a web-based survey - Alves, Claudia (2024)
Introduction and Objectives: Autoimmune liver diseases (AILD), including autoimmune hepatitis (AIH), primary biliary cholangitis (PBC), and primary sclerosing cholangitis (PSC), are chronic immune-mediated liver conditions. This study aimed to assess the reality of AILD in Latin America (LA).